The Military and Civil Supremacy in Indonesian Democracy: Towards an Ideal Model in Siyāsah Sharʻiyyah Perspective - Suntoro, Agus (Al-Risalah, 2019)
In the history of Indonesia, civil-military relations changed in the reformasi era with the separation of the military and the police, resulting in the removal of the dual-function doctrine and military reform. Despite so, two decades after reformasi has not formed a standard and ideal mechanism to govern civil-military relations within the framework of objective civilian control. This paper addresses issues regarding (a) how the dual-function concept and internal reform within the military; (b) regulatory issues that govern military operations other than war; (c) the ideal model of civil-military relations in Indonesia to ensure democratic life and an overview of the siyāsah sharʻiyyah aspects. Using descriptive qualitative method and conducting discussions with military and human rights experts, this paper demonstrates that military reform in Indonesia after the New Order has not yet been fruitful to accomplish the mission to form professional soldiers. The military is still involved in political and civilian life under the pretext that there is no military assistance law. As a consequence, the ideal model of civilian control that puts the military under the control of civilian authority according to siyāsah sharʻiyyah principle has not been fully successful and effective.